IOT SENSOR TECHNOLOGY AND CLOUD APPLICATION ON FARMING PRACTICE: PLANT LIVE DATA MONITOR IN AGRICULTURE - Ane, Tanjea; Nepa, Tabatshum; Khan, Mahfuzur Rahman (Bangladesh Journal of Multidisciplinary Scientific Research, 2023)
Modern farming practices place high importance on cutting-edge technology for plant data monitoring since data monitoring enables farmers to promote sustainable farming practices in fieldwork. World agriculture forwards looking at sustainable management practices in agricultural farms. Real-time of plant data monitoring gets priority in precision farming making farmers informed plant decisions. The study’s aim is to design a sensor and cloud application for farmers’ plants’ live data monitor that provides an opportunity for earlier disease and pest detection to control long-term and effective agricultural development as well as provides sensor wireless network support to track plants’ natural characteristics and anomalies detection. This research investigates sensor applications in farming practices to collect plant live data to produce information before making decisions about plants. Application applied MySQL cloud database to store plants analog data, virtually smart devices connect farmers access with plants field. The article experiment reveals that remote farmers can direct plants’ current condition in the environment. Farmers get support to make immediate actions based on live data behavior in an innovative way thus fast response for plants improves the quality of production also optimizes resource use. A study found live data monitoring with a sensor network and cloud server application provides a technology-driven data collection model that efficiently analyzes data interpretation for farming practices. JEL Classification Codes: Q110, Q130, Q160.